Corbino : from Rubens to Ringling - Londraville, Janis (Excelsior editions, 2011)
The family. Blood -- Immigrant -- The artist. Apprentice -- The Rubens of New England -- Disaster -- An American art -- In love and death -- The transformation. Toil and trouble -- A fistful of snakes -- Flying free -- Crucified -- The unraveling. Last love -- Cracks -- The American dream -- Shocks and sunshine -- Finale. At the same time -- Death of the dream -- Epilogue for an artist